2021
DOI: 10.1101/2021.05.06.21256651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher case fatality rate among obstetric patients with COVID-19 in the second year of pandemic in Brazil: do new genetic variants play a role?

Abstract: Background: In Brazil, a 20% increase in maternal mortality rate due to COVID-19 is projected for 2020. On January 4, 2021, the P.1 SARS-CoV-2 genetic variant was firstly identified in the country and recent data has indicated an association with higher hospitalization rates and mortality. The impact of P.1 variant in the obstetric population remains unclear. Methods: We carried out a preliminary analysis of sociodemographic and clinical characteristics of COVID-19 confirmed maternal deaths (between 10-50 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
(9 reference statements)
0
8
1
Order By: Relevance
“…Being able to compare the maternal population to other subgroups allowed us to observe that the effect of COVID-19 related mortality on pregnant and postpartum women was not equally present in the rest of the population during the 2021 pandemic year. This conclusion is different from other studies which analyze the maternal group independently [12][13][14][15][16][17][18][19][20][21][22][23][24]. Therefore, our study is unique in comparing symptoms, comorbidities, and outcomes between the maternal patients and the rest of the population and between the different pandemic years [16].…”
Section: Plos Onecontrasting
confidence: 61%
See 1 more Smart Citation
“…Being able to compare the maternal population to other subgroups allowed us to observe that the effect of COVID-19 related mortality on pregnant and postpartum women was not equally present in the rest of the population during the 2021 pandemic year. This conclusion is different from other studies which analyze the maternal group independently [12][13][14][15][16][17][18][19][20][21][22][23][24]. Therefore, our study is unique in comparing symptoms, comorbidities, and outcomes between the maternal patients and the rest of the population and between the different pandemic years [16].…”
Section: Plos Onecontrasting
confidence: 61%
“…In early 2021, the maternal mortality rate seems to be even higher, even though the knowledge about the disease and the treatment tools have evolved. A recent study by Takemoto et al, demonstrated that the mortality rate was about two times higher for the maternal population in 2021 (15.6%), when compared to 2020 (7.4%) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 21 Similarly, the authors of a recent Brazilian study hypothesized that increased maternal mortality rates in 2021 relative to 2020 may be related to the rise of the Gamma variant. 22 During the period of Gamma variant predominance, a higher risk of death and severe COVID‐19 outcomes among pregnant and postpartum women was observed in Brazil. 23 …”
Section: Epidemiology and Outcomes Of Covid‐19 During Pregnancymentioning
confidence: 99%
“…In Mississippi in the United States, an apparent increase in COVID‐19–associated deaths among pregnant women was observed after the Delta variant became the predominant strain (pre‐Delta period, five deaths per 1000 infections during pregnancy; Delta predominance period, 25 deaths per 1000) 21 . Similarly, the authors of a recent Brazilian study hypothesized that increased maternal mortality rates in 2021 relative to 2020 may be related to the rise of the Gamma variant 22 . During the period of Gamma variant predominance, a higher risk of death and severe COVID‐19 outcomes among pregnant and postpartum women was observed in Brazil 23 …”
Section: Epidemiology and Outcomes Of Covid‐19 During Pregnancymentioning
confidence: 99%
“…The numbers of pregnant and postpartum women in the UK admitted to hospital or intensive care because of covid-19 peaked over the summer 1. Maternal mortality has reached concerning levels in 2021, with case fatality rates rising in the US, doubling in Brazil, and almost tripling in India since the beginning of the pandemic 234. In Brazil, health officials even suggested avoiding pregnancy to reduce risk during the pandemic 5…”
mentioning
confidence: 99%